2013
DOI: 10.1371/journal.pone.0054846
|View full text |Cite
|
Sign up to set email alerts
|

The Immediately Releasable Pool of Mouse Chromaffin Cell Vesicles Is Coupled to P/Q-Type Calcium Channels via the Synaptic Protein Interaction Site

Abstract: It is generally accepted that the immediately releasable pool is a group of readily releasable vesicles that are closely associated with voltage dependent Ca2+ channels. We have previously shown that exocytosis of this pool is specifically coupled to P/Q Ca2+ current. Accordingly, in the present work we found that the Ca2+ current flowing through P/Q-type Ca2+ channels is 8 times more effective at inducing exocytosis in response to short stimuli than the current carried by L-type channels. To investigate the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(53 citation statements)
references
References 61 publications
4
48
0
1
Order By: Relevance
“…The ensuing entry of calcium ions then triggers the fusion of synaptic vesicles, culminating in the release of neurotransmitters into the synaptic cleft. The three major Ca V 2 channel isoforms support not only rapid neurotransmitter release but also hormone release from secretory cells such as chromaffin cells (Santana et al, 1999;Albillos et al, 2000;Wykes et al, 2007;Álvarez et al, 2013).…”
Section: B Physiologic Roles Of Ca V 2 Calcium Channelsmentioning
confidence: 99%
“…The ensuing entry of calcium ions then triggers the fusion of synaptic vesicles, culminating in the release of neurotransmitters into the synaptic cleft. The three major Ca V 2 channel isoforms support not only rapid neurotransmitter release but also hormone release from secretory cells such as chromaffin cells (Santana et al, 1999;Albillos et al, 2000;Wykes et al, 2007;Álvarez et al, 2013).…”
Section: B Physiologic Roles Of Ca V 2 Calcium Channelsmentioning
confidence: 99%
“…The most recognized and well characterized voltage sensors in excitable cells are voltage‐dependent ion channels. It is known that some VDCC are functionally and spatially associated with the exocytotic machinery and with immediately releasable vesicles in neurons and neuroendocrine cells . Therefore, VDCC are major candidates to be the voltage sensors responsible of CIVDE.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the addition of an exogenous free synprint peptide that competes with the endogenous synprint site of the Ca 2+ channel molecule disrupts vesicle‐channel interaction and inhibits neurotransmission . Particularly in chromaffin cells we showed previously that the exocytosis of IRP is markedly reduced in presence of the free synprint, and concluded that synprint is important in the coupling between IRP vesicles and P/Q‐type Ca 2+ channels . In order to evaluate if synprint mediates CIVDE, we transfected our cells with an IRES plasmid encoding the synprint peptide and EGFP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative mechanism for the preferential role of Ca V 2.2 in somatodendritic release of OT is an interaction between the synprint site and exocytotic proteins. The immediately releasable pool of granules in mouse chromaffin cells is coupled to Ca V 2.1 channels through an interaction mediated by the synprint site and whole cell capacitance measurements have suggested that a rapidly releasable pool of granules exists in MNC somata . It is therefore possible that a pool of granules in OT MNC somata may be coupled to Ca V 2.2 channels via an interaction between the synprint site and the complexes of exocytotic proteins attached to those granules.…”
Section: Discussionmentioning
confidence: 99%